Gambaran Kesiapan Perawat Ruang Rawat Inap Terhadap Implementasi Telenursing Dalam Upaya Meningkatkan Mutu Pelayanan Rumah Sakit - Humam Khoironi; Eko Susilo (Universitas Ngudi Waluyo, 2019)
In its use, Indonesia reaches 150 million people with a penetration of 56% which is well known throughout the region. This phenomenon was influenced by the development of Revolution 5.0 which was initiated by the Japanese inventor with the concept of Society 5.0 as an anticipation of global trends as the impact of the 4.0 industrial revolution trend. Teleursing is expected to be a solution in addressing this challenge in order to improve the quality of hospital services.The results showed that only 29 respondents with low technical readiness (22.0%), 89 (67.4%) moderate readiness and 14 (10.6%) high readiness respondents. according to nursing readiness data obtained were low readiness of 9 (6.8%) medium of 101 (76.5%) and high readiness of 22 (16.7%) of respondents. And according to communication readiness data obtained 3 low readiness (2.3%) moderate for 74 (56.1%) and with high readiness as many as 55 (41.7%) respondents. This study used a quantitative descriptive design using a quantum sampling technique with a questionnaire measuring instrument. This research, it is hoped that there will be a wider regulation, training, socialization and making a special telenursing application to support the implementation of telenursing.Keywords: Telenursing Implementation,Nurse Preparedness, Quality of Nursing Services